2005
DOI: 10.1007/s11259-005-3080-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Studies on the Testis of Korean Ring-necked Pheasant (Phasianus colchicus karpowi) during the Breeding and Non-breeding Seasons

Abstract: The purpose of this study was to obtain detailed quantitative information on all cell types in the testis interstitium of Korean ring-necked pheasants and to combine these data with changes in the steroidogenic function of the testis during the breeding and non-breeding seasons. For animals collected during the breeding season, their testis weights, sperm production, serum testosterone levels and leuteinizing hormone (LH)-stimulated testosterone secretion were significantly (p < 0.01) increased compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
2
7
0
2
Order By: Relevance
“…However, the proportions of interstitium vary among species and between gonadally inactive and active states. For example, the interstitial area in gonadally inactive and active states has been reported to be 27.5 and 12.5% in the Emu (Malecki et al 1998) and 32.4 and 6.75% in the Korean Ring-necked Pheasant (Tae et al 2005); for the Jungle Crow, we obtained values of 44.43 and 7.89%, respectively, in our study.…”
Section: Discussionsupporting
confidence: 61%
“…However, the proportions of interstitium vary among species and between gonadally inactive and active states. For example, the interstitial area in gonadally inactive and active states has been reported to be 27.5 and 12.5% in the Emu (Malecki et al 1998) and 32.4 and 6.75% in the Korean Ring-necked Pheasant (Tae et al 2005); for the Jungle Crow, we obtained values of 44.43 and 7.89%, respectively, in our study.…”
Section: Discussionsupporting
confidence: 61%
“…The present study provides a detailed morphological description of the reproductive system of the smooth‐billed ani and reports about intense reproductive remodeling as evidence of opportunistic breeding behavior following rainfall variations in a semiarid area. The findings of this study (1) showed that the reproductive morphology of the smooth‐billed ani was similar to that observed in other birds such as domestic quail, fowl, emu, ostrich, goose, parakeet and drake (Aire, 2002; Aire & Soley, 2000; Leska, Kiezun, Kaminska, & Dusza, 2015; Parizzi et al, 2008; Peixoto et al, ; Reed, Cope, & Blackford, 2011); (2) indicated intense gonadal activity throughout the wet season that was consistently similar to what is described in other birds during the breeding season (Baraldi‐Artoni et al, ; Kim & Yang, ; Leska & Dusza, ; Peixoto et al, ; Tae et al, ); (3) and revealed remarkable signs of gonadal involution and low gametogenic activity after precipitation decreased. Birds inhabiting areas with adverse climate characteristics exhibit flexibility with regard to the timing and intensification of breeding activity whenever environmental conditions are satisfactory to ensure reproductive success and offspring survival (Cruz‐McDonnell & Wolf, ; Dybala, Eadie, Gardali, Seavy, & Herzog, ; Quintero, González‐Caro, Zalamea, & Cadena, ; Sandoval, ; Selwood et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Histological and morphometric analyses revealed that gander testes undergo marked structural seasonal changes as it has been described in Bilgoraj goose (Anser anser) and Canadian goose (Branta canadensis) [28,31,32] and other bird species [1,20,25,42]. Interestingly, structural changes in testicular tissue in the sexual reactivation phase remain weakly researched, especially in geese.…”
Section: Discussionmentioning
confidence: 96%